Probability-based Equation for Predicting Mortality in COVID-19 Patients - Pande Putu Dimas Yoga Pratama; I Made Wisnu Wardhana; Made Dharmesti Wijaya (Publication Department, Universitas Warmadewa, 2024)
Background The global mortality rate for coronavirus disease-2019 (COVID-19) continues to climb. The study goal is to provide a proper equation to predict mortality in COVID-19 patients based on medical history, and laboratory examination Methods This was a case-control study. Patients with COVID-19 confirmed case was taken for medical history, physical, and laboratory examination. CBC and D-Dimer were checked when patients were admitted to the hospital. Statistical analysis that was use include Chi-Square or Fisher’s test as comparative study, risk estimate for odds ratio, and logistic regression to formulated the equation. Results Ninety-six patients were gathered at the end of study. The study grouped patients based on survival at end of care which is life and death as dependent variable. We also grouped patients based on several parameter like geriatric age, comorbidities, symptoms (fever, cough, anosmia, cold, dysphagia, and shortness of breath), anemia, leukocytosis/leukopenia, thrombocytopenia, elevated D-Dimer, and pneumonia, as independent variables. Geriatric, comorbidities, fever, cough, shortness of breath, anemia, leukocytosis/leucopenia, lymphopenia, and elevated D-Dimer had significant differences with p < 0.05. Odds ratio and 95%CI for these parameters were 3.02 (1.11-8.20), 4.07 (1.35-12.27), 3.57 (0.96-13.23), 5.04 (1.08-23.34), 4.75 (1.02-22.02), 3.26 (1.15-9.25), 6.40 (2.19-18.63), 3.16 (0.97-10.30), and 0.70 (0.61-0.81), respectively. Multivariate analysis using logistic regression based on this result was calculated and we were able to make this probability equation, p = 1/(1+e-y), with e =2.7, and y = - 24.99 + 1.621(comorbidities) + 1.944(cough) + 1.643(leukocytosis/leukopenia) + 1.397(anemia) + 20.625(elevated D-Dimer). ROC was use to confirm this predicted probability with AUC 0.88 Conclusion This equation was simple enough to be used as tool for clinician to predict mortality in COVID-19 patients. If we were to assume that for example patient with COVID-19 with comorbidities had cough as symptoms, and also had leukocytosis/leukopenia, anemia, and elevated D-Dimer level based on laboratory result, then that patient had 90.25% probability of death as outcome. The study was able to predict death in COVID-19 patients with up to 90.25% probability using our equation with excellent discrimination between these patients